Analysis of the Influence of Operating Leverage and Dividend Policy on the Value of Companies with Capital Structure as a Variable Intervening of the Indonesia Stock Exchange - Masno Marjohan (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the effect of operating leverage and dividend policy on firm value with capital structure as an intervention variable. The population of this study were food and beverage companies listed on the Indonesia Stock Exchange in the 2016-2020 period, namely 26 companies. The sample in this study amounted to 10 companies and had 50 observational data that had been selected using the purposive sampling method. The data used in this study is secondary data obtained from the Indonesia Stock Exchange (IDX) and data analysis using regression analysis. The results show that operating leverage has a negative and insignificant effect on firm value, dividend policy has a positive and insignificant effect on firm value, and operating leverage has a negative and significant effect on firm value with capital structure as an intervening variable, dividend policy has a negative effect and significant to capital structure mediated by firm value, capital structure has no positive and insignificant effect on firm value, capital structure mediates the effect of dividend policy on firm value, capital structure has a positive and significant effect on firm value.